Modeling and Computer Simulation - Cvetković, Dragan (IntechOpen, 2019)
Computer simulation or a computer model has the task of simulating the behaviour of an abstract model of a particular system. Computer simulations have become a useful part of mathematical modeling of many natural systems in physics, quantum mechanics, chemistry, biology, economic systems, psychology, and social sciences, as well as in the engineering process of new technologies. The authors of the five chapters have presented various applications of computer simulations as well as their advantages and disadvantages. They describe the process of modeling and its simulation of heat recovery steam generators, the chronometer detent escapement mechanism, relevant sociotechnical processes with regard to new housing and building law and regional management trends in the European Union, and the agent-based model for biological systems.